Cochlear Implantation and Single-sided Deafness: A Systematic Review of the Literature - Cabral Junior, Francisco; Pinna, Mariana Hausen; Alves, Ricardo Dourado; Malerbi, Andrea Felice dos Santos; Bento, Ricardo Ferreira (International Archives of Otorhinolaryngology, 2016)
Introduction Current data show that binaural hearing is superior to unilateral hearing, specifically in the understanding of speech in noisy environments. Furthermore, unilateral hearing reduce onés ability to localize sound.Objectives This study provides a systematic review of recent studies to evaluate the outcomes of cochlear implantation in patients with single-sided deafness (SSD) with regards to speech discrimination, sound localization and tinnitus suppression.Data Synthesis We performed a search in the PubMed, Cochrane Library and Lilacs databases to assess studies related to cochlear implantation in patients with unilateral deafness. After critical appraisal, eleven studies were selected for data extraction and analysis of demographic, study design and outcome data.Conclusion Although some studies have shown encouraging results on cochlear implantation and SSD, all fail to provide a high level of evidence. Larger studies are necessary to define the tangible benefits of cochlear implantation in patients with SSD.
Keywords: unilateral hearing loss; cochlear implantation; single-sided deafness; speech discrimination; sound localization; tinnitus